Signum temporis? Rosyjsko-ukraiński spór językowy w kontekście europejskich transformacji tożsamościowych (Politeja, 2025)
SIGNUM TEMPORIS? THE RUSSIAN-UKRAINIAN LANGUAGE DISPUTE IN THE CONTEXT OF EUROPEAN IDENTITY TRANSFORMATIONSThe article explores the idea that late modernity is partly characterised by linguistic conflicts, arising from clashes between complex communication and value-based structures. They reflect differing attitudes toward the modern era, resulting in various strategies for transcending it. Moreover, linguistic collisions are compared to religious ones, greatly impacting Europe’s modern self-recognition during the Reformation and Counter-Reformation periods. In this context: 1. Heinz Schilling’s overview of 16th- and 17th-century religious and confessional conflicts is employed as a model for in-depth understanding of multidimensional identity confrontations; 2. the Russian-Ukrainian war is portrayed as a result of complex linguistic dissent, representing vital identity polarization of our time; 3. it is argued that today’s evolution of communication and value-based structures amplifies the discord among postmodern identities (e.g., European identity founded on the principle of unification in diversity vs. Russian identity founded on the principle of unification through domination).